Effect of radio frequency heating on yoghurt – I. Technological applicability, shelf-life and sensorial quality. - Siefarth, Caroline; Tran, Thi Bich Thao; Mittermaier, Peter; Pfeiffer, Thomas; Büttner, Andrea (Foods, 2014)
This first part of a two-part study focuses on the technical feasibility of applying radio frequency (RF) heating at different temperatures (58, 65 and 72 °C) to a stirred yoghurt gel after culturing. For comparison, a convectional (CV) heating process was also applied. The aim was to increase the yoghurt shelf-life, by preventing post-acidification and the growth of yeasts and molds. At the same time, the viability of lactic acid bacteria (LAB) was investigated in view of existing legal regulations for yoghurts. Additionally, the yoghurt color, aroma and taste profiles were evaluated. It was found that the application of RF heating was effective for the rapid attainment of homogenous temperatures of 58 and 65 °C, respectively. For RF heating at 72 °C, it was not possible to establish a stable heating regime, since in some cases, there was significant overheating followed by strong contraction of the yoghurt curd and whey separation. Hence, it was decided not to continue with the RF heating series at 72 °C. In the case of CV heating, heat transfer limitations were observed, and prolonged heating was required. Nevertheless, we showed that yeasts and molds survived neither the RF nor CV heat treatment. LAB were found not to survive the CV treatment, but these beneficial microorganisms were still present in reduced numbers after RF heating to 58 and 65 °C. This important observation is most likely related to the mildness of RF treatment. While post-acidification was not observed on yoghurt storage, slight color changes occurred after heat treatment. The flavor and taste profiles were shown to be similar to the reference product. Furthermore, a trained sensory panel was not able to distinguish between, for example, the reference yoghurt and the RF 65 °C sample by triangular testing (α = 5%), showing the potential of novel strategies for further improvements of heat-treated yoghurt.<br